High-dose Melphalan-based Autotransplants for Multiple Myeloma: The Arkansas Experience Since 1989 in 3077 Patients - Pineda-Roman, Mauricio (2008)
BACKGROUND: In this report, the authors describe their collective experience with melphalan-based autotransplants since the inception of their program at the University of Arkansas for Medical Sciences in 1989. METHODS: The authors evaluated the clinical outcomes of 3077 successive patients with multiple myeloma (MM) who underwent at least 1 melphalan-based autotransplantation at the University of Arkansas. Of these, 1078 patients were enrolled on front-line Total Therapy (TT) protocols (TT-P) TT1, TT2, and TT3; 1104 patients were entered on protocols for newly diagnosed or previously treated patients (non-TT-P); and 895 patients were treated off protocol (non-P). RESULTS: The 10-year overall survival (OS) rates after first transplantation were 41%, 19%, and 11% (P < .001) for the TT-P, non-TT-P, and non-P groups, respectively. In the TT-P group, the median OS was 72 months on TT1, was not reached at ≥7 years on TT2, and was 88% at 2 years on TT3. Among 2683 patients with complete baseline data, absence of hypodiploidy/chromosome 13 deletion, β-(2)-microglobulin <3.0 mg/L, C-reactive protein <6 mg/L, albumin ≥3.0 g/dL, and platelet count ≥100,000/μL all were associated independently with superior OS (P < .001), event-free survival (P < .001), and duration of complete remission (P < .001). CONCLUSIONS: The results from this large, single-institution experience demonstrated that >10-year OS was accomplished in >40% of all patients enrolled on TT-P, whereas such success was observed in only 15% of the remaining patients (including 25% in the presence of all 5 good-risk features). Superior outcomes with protocol-based, primary transplant regimens such as TT-P draw attention to the importance of applying the best available therapies upfront.